OPTIMALISASI SISTEM INFORMASI KEUANGAN DAERAH PADA ORGANISASI PERANGKAT DAERAH KOTA BANDUNG - Komala, Adeh Ratna; Hendarin, Deri (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2021)
Abstract This study aims to examine the effect of the implementation of regional financial accounting information systems on the quality of regional financial reports that are in the Regional Apparatus Organization in Bandung. The phenomenon of this research is financial statements with unqualified and incomplete opinions. The research method is descriptive method of verification where the unit of analysis is the Bandung City Regional Apparatus Organization as many as 27 Regional Apparatus Organizations with 46 respondents. Testing data using validity and reliability tests using SPSS V 24 for testing data analysis and using SmartPLS V3 for hypothesis testing. The results showed that the local government financial accounting information system had an effect on the quality of local government financial reports. Keywords: regional financial accounting information system, quality of local government financial reports